Nutrition : a health promotion approach / Geoffrey P. Webb. - Webb, Geoffrey P. (Arnold, 2002)
Covering the whole field of nutrition, this book focuses on areas considered to be a priority for promoting health in industrialised countries. The new edition includes more on health promotion theory.